Service employees' fit, work-family conflict, and work engagement - Karatepe, Osman M.; Karadas, Georgiana (Emerald Group Publishing Ltd, 2016)
Purpose - Using person-job fit, congruence and conservation of resources theories as the theoretical underpinnings, the purpose of this study is to propose and test a research model that investigates work-family conflict and family-work conflict as mediators of the impact of person-job fit on work engagement. The model also examines the mediating role of work engagement in the relationship between conflicts in the work-family interface and life satisfaction. Design/methodology/approach - Data gathered from frontline hotel employees two weeks apart in three waves in Romania were utilized to assess the abovementioned relationships via structural equation modeling. Findings - Two directions of conflict act as partial mediators between person-job fit and work engagement. Work engagement fully mediates the relationship between work-family conflict and life satisfaction, while it functions as a partial mediator of the effect of family-work conflict on life satisfaction. Originality/value - This paper contributes to current knowledge by investigating the interrelationships of person-job fit, two directions of conflict, work engagement and life satisfaction.
Keywords: Work engagement; Romania; Work-family conflict; Life satisfaction; Person-job fit